Concepts of speaking, writing, reading and listening in German language teaching - Xurramova Soxiba (Zien Journals, 2022)
This scientific paper discusses 4 Conpetences in German—the ability to speak, read, write, and listen and understand.
Keywords: speech; reading; writing